Judith Butler: un formidable “error” de traducción (primer parte) - Milone, Jerônimo (2020)
This article analyzes the Argentinean translation of the book Who Sings the Nation-State?, by Butler and Spivak, a book that examines the relationship between translation and national anthem, so as to suggest the possibility of nationalism related to specific political manifestations. Despite its own insistence onthe necessity of an incli-nation to sing the anthem, however, in the English original edition commits a “mistake” in the transcription of “Il [sic] pueblo unido jamás sera [sic] vencido”. But what if this were no simple accident, but an intended “mistake”, a performative contradiction? With what incli-nation, that is, might Butler have quoted this song? And what meaning can be ascribed to the fact that, while we might, on the one hand, suspect the political manifestations described by the book to be a form of nationalism, on the other hand, this seems not to be the case, since the Argentinean translation “corrects” these mistakes and, at the same time, testifies, in a footnote, that the quotations are “En español en el original”? By analyzing these dead ends of translation, this article aims to indicate the political consequences of the task of the translator, and the ways in which literature transgresses grammar.